Brain atrophy in primary age‐related tauopathy is linked to transactive response DNA‐binding protein of 43 kDa. Issue 6 (2nd May 2019) - Josephs, Keith A.; Murray, Melissa E.; Tosakulwong, Nirubol; Weigand, Stephen D.; Knopman, David S.; Petersen, Ronald C.; Jack, Clifford R.; Whitwell, Jennifer L.; Dickson, Dennis W.
Abstract: Introduction: Primary age‐related tauopathy (PART) is characterized by the presence of neurofibrillary tangles and absent‐minimal β‐amyloid deposition. Transactive response DNA‐binding protein of 43 kDa (TDP‐43), a third protein, has recently garnished a lot of attention in Alzheimer's disease where it is associated with memory loss and amygdala and hippocampal atrophy. We aimed to determine whether TDP‐43 is associated with brain atrophy in PART. Methods: We assessed the frequency of TDP‐43 in PART and performed voxel‐level analysis in SPM12, as well as region‐of‐interest analysis using linear regression modeling, controlling for variables of interest, to assess for associations between TDP‐43 and brain atrophy. Results: Of 116 PART cases, 31 (26.7%) had TDP‐43. The presence of TDP‐43 was associated with significantly greater amygdala, hippocampal, and anterior temporal atrophy in both the region‐of‐interest and the voxel level analyses. Discussion: TDP‐43 is associated with greater brain atrophy in PART.